Long‐term use of foscarnet is associated with an increased incidence of acute kidney injury in hematopoietic stem cell transplant patients: A retrospective observational study. Issue 2 (10th February 2022) - Inose, Ryo; Takahashi, Katsuyuki; Takahashi, Masaya; Sugimoto, Takashi; Nanno, Satoru; Hino, Masayuki; Nagayama, Katsuya
Abstract: Background: Foscarnet is an important drug for the treatment of cytomegalovirus infection in patients undergoing hematopoietic stem cell transplantation (HSCT). Foscarnet is often discontinued because of the development of acute kidney injury (AKI). Thus, the identification of factors leading to the development of AKI is beneficial. This study aimed to investigate the incidence of AKI and the factors influencing AKI development in HSCT patients treated with foscarnet. Methods: This was a retrospective observational study. Patients who underwent HSCT and received foscarnet at the Department of Hematology, Osaka City University Hospital, were identified from medical records. The patients were classified into AKI and non‐AKI groups, and the risk factors associated with AKI were evaluated. For continuous variables, receiver‐operating characteristic (ROC) curve analysis was used to calculate the optimal cutoff value. Results: Thirty‐five patients (47 cases) were assigned to the AKI (51.1%, 24/47) and non‐AKI groups (48.9%, 23/47). The AKI group had a significantly longer foscarnet administration period than the non‐AKI group ( p = 0.049). The appropriate cutoff value for the foscarnet administration period using the ROC curve was 27 days. The incidence of AKI was significantly higher in cases who received foscarnet for more than 27 days (11/14, 78.6%) compared to those who received less than 27 days (13/33, 39.4%) (odds ratio: 5.64, 95% confidence interval 1.32–24.2, p = 0.024). Conclusion: The incidence of AKI was 51.1% in HSCT patients treated with foscarnet, and foscarnet administration for more than 27 days may be associated with the incidence of AKI.